Bilateral Primary Total Knee Arthroplasty and Reconstruction of the Medial Tibial Plateau by an Asymmetric Cone in a Patient with Charcot Arthropathy - Spiros Tsamassiotis; Henning Windhagen; Max Ettinger (Case Reports in Surgery)
Charcot arthropathy of the knee is an extremely rare orthopedic disease that is very challenging for the treating physician and is associated with many complications, especially if it is occurring on both knees. Meanwhile, in the advanced stage, despite many potential complications, TKA is recognized as the gold standard. However, destruction of the medial tibial plateau is typical for the disease, which makes a stable anchorage of the prosthesis much more difficult. Therefore, we present a case in which sufficient primary stability could be achieved with an asymmetrical second-generation tibial cone with an anatomical design and implantation instruments adapted to the bony anatomy in the presence of severe tibial destruction on both sides. In the two-year follow-up, the patient showed good mobility and stability on both sides. In advanced Charcot arthropathy of the knee, the use of asymmetric tibial cones appears to be an appropriate solution for secure fixation and stability of the implant.